2022
DOI: 10.1186/s12944-022-01667-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating growth differentiation factor 15 levels and apolipoprotein B to apolipoprotein A1 ratio in coronary artery disease patients with type 2 diabetes mellitus

Abstract: Background Clinical investigations have found that there was a close association between T2DM and adverse cardiovascular events, with possible mechanisms included inflammation, apoptosis, and lipid metabolism disorders. High serum GDF-15 concentration and the apolipoprotein B/apolipoprotein A1 ratio (ApoB/ApoA1) are involved in the above-mentioned mechanisms and are thought to be related to the occurrence of adverse cardiovascular events. However, it remains unclear whether circulating GDF-15 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…25) Among diabetic patients with CAD, some studies have shown that the ApoB/ApoA 1 ratio of diabetic (type 2 DM) patients with CAD was significantly higher than that of patients with type 2 DM alone, and the ratio was helpful to predict the occurrence of CAD in patients with type 2 DM. 26) Our study demonstrated that the ApoB/ApoA1 ratio was an independent risk factor and a certain predictive value for the RP of NCCLs, and the predictive value was significantly better than ApoA1, ApoB, and the LDL-C/HDL-C ratio. In addi-tion, in the 108 patients with a higher initial ApoB/ApoA1 ratio whose ApoB/ApoA1 ratio was !…”
Section: Discussionsupporting
confidence: 48%
“…25) Among diabetic patients with CAD, some studies have shown that the ApoB/ApoA 1 ratio of diabetic (type 2 DM) patients with CAD was significantly higher than that of patients with type 2 DM alone, and the ratio was helpful to predict the occurrence of CAD in patients with type 2 DM. 26) Our study demonstrated that the ApoB/ApoA1 ratio was an independent risk factor and a certain predictive value for the RP of NCCLs, and the predictive value was significantly better than ApoA1, ApoB, and the LDL-C/HDL-C ratio. In addi-tion, in the 108 patients with a higher initial ApoB/ApoA1 ratio whose ApoB/ApoA1 ratio was !…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, CAD was positively correlated with serum GDF-15 or ApoB/ ApoA1 ratio. They suggested that these markers may help predict the occurrence of CAD in patients with T2D [13]. In another study, Haller et al found that hs-cTnI, NT-proBNP, and hs-CRP were independently associated with cardiovascular events and can improve cardiovascular risk prediction [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while indicated in certain situations, diagnostic interventions, including cardiac exercise test, cardiac radionuclide scan, computed tomography (CT) angiography, and cardiac catheterization, are costly and come with several associated complications [ 12 ]. Consequently, for early diagnosis and screening of high-risk patients, the tendency to use biochemical markers has increased [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the levels of Lpa and APO-B increase and the level of APO-A decreases, the risk of MCA stenosis occurs. Mei Y, 2022 40 China Case-Control Patients with coronary artery disease and type 2 diabetes mellitus To evaluate and compare the ApoB/ApoA1 ratio and GDF-15 concentrations in T2DM patients with or without CAD and examine their ability to predict CAD. Coronary Artery disease 502 Circulating GDF-15 levels and serum ApoB/ApoA1 ratio vary in CAD group and T2DM group.…”
Section: Introductionmentioning
confidence: 99%